2018
DOI: 10.1002/da.22835
|View full text |Cite
|
Sign up to set email alerts
|

Differences between chronic and nonchronic depression: Systematic review and implications for treatment

Abstract: Background: There is still uncertainty if and to what extent chronic depression (CD) presents with specific features especially in contrast to the nonchronic course of major depressive disorder (non-CD). This systematic review aims to summarize the existing literature regarding sociodemographic factors, psychopathology, and course of disease in patients with CD in comparison to patients with non-CD. Methods: A structured database search (MEDLINE, PsycINFO, Web of Science, CENTRAL) was performed. All studies co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 52 publications
(225 reference statements)
5
36
0
3
Order By: Relevance
“…On the individual level, there was a remarkably higher prevalence of current depressive symptoms (as assessed by PHQ-9) among PDD cases than among NCMDD cases, as well as a higher mean number of depressive episodes (irrespective of episode severity or duration). Furthermore, higher levels of psychological and somatic comorbidity are in line with international findings on higher comorbidity rates [12,14,15,18,20,22] and somatic morbidity [14,15] for chronic depression courses. The present outcomes of worse self-rated health and reduced health-related quality of life for the MCS correspond to previous findings of reduced psychological well-being and health-related quality of life for individuals with chronic depression [12][13][14]23].…”
Section: Higher Disease Burden For Chronic Vs Non-chronic Depressionsupporting
confidence: 86%
See 4 more Smart Citations
“…On the individual level, there was a remarkably higher prevalence of current depressive symptoms (as assessed by PHQ-9) among PDD cases than among NCMDD cases, as well as a higher mean number of depressive episodes (irrespective of episode severity or duration). Furthermore, higher levels of psychological and somatic comorbidity are in line with international findings on higher comorbidity rates [12,14,15,18,20,22] and somatic morbidity [14,15] for chronic depression courses. The present outcomes of worse self-rated health and reduced health-related quality of life for the MCS correspond to previous findings of reduced psychological well-being and health-related quality of life for individuals with chronic depression [12][13][14]23].…”
Section: Higher Disease Burden For Chronic Vs Non-chronic Depressionsupporting
confidence: 86%
“…Recent reviews found that patients with PDD more often have psychiatric comorbidities than those with non-PDD, particularly personality disorders but also axis I and somatic comorbidities [22]. However, differences between PDD and NCMDD cases in DEGS1-MH have only been observed by trend, and our clinical sample of PDD patients demonstrated even less comorbidity than interview-defined cases.…”
Section: More Severe Pdd Cases In the Health Care Systemmentioning
confidence: 53%
See 3 more Smart Citations